Enhancement of Affective Processing Induced by Bifrontal Transcranial Direct Current Stimulation in Patients With Major Depression. Issue 2 (24th May 2013) - Brunoni, Andre Russowsky; Zanao, Tamires Araujo; Vanderhasselt, Marie‐Anne; Valiengo, Leandro; de, Janaina Farias; Boggio, Paulo S.; Lotufo, Paulo A.; Benseñor, Isabela M.; Fregni, Felipe
<x xml:space="preserve">Abstract</x> Objective Our aim was to evaluate whether one single section of transcranial direct current stimulation (tDCS), a neuromodulatory technique that noninvasively modifies cortical excitability, could induce acute changes in the negative attentional bias in patients with major depression. Subjects and Methods Randomized, double‐blind, sham‐controlled, parallel design enrolling 24 age‐, gender‐matched, drug‐free, depressed subjects. Anode and cathode were placed over the left and right dorsolateral prefrontal cortex. We performed a word Emotional Stroop Task collecting the response times (RTs) for positive‐, negative‐, and neutral‐related words. The emotional Stroop effect for negative vs. neutral and vs. positive words was used as the measure of attentional bias. Results At baseline, RTs were significantly slower for negative vs. positive words. We found that active but not sham tDCS significantly modified the negative attentional bias, abolishing slower RT for negative words. Conclusion Active but not sham tDCS significantly modified the negative attentional bias. These findings add evidence that a single tDCS session transiently induces potent changes in affective processing, which might be one of the mechanisms of tDCS underlying mood changes.